ANALISIS KINERJA DAN PENGEMBANGAN PELABUHAN LAUT DI BALI (STUDI KASUS: PELABUHAN CELUKAN BAWANG) - Kadek Arisena Wikarma; I W Suweda; I G. Putu Suparsa (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2016)
Abstract: Celukan Bawang Harbour is located in the northern province of Bali. Port traffic through the Celukan Bawang Harbour during the period of 2005-2009 has decreased. So It is necessary for the performance evaluation of the port so that the reduction in traffic flows of goods can be determined. In addition, this study also predict traffic flow of goods 30 years future so it can be evaluated development of the port in the future . The evaluation was done based on the performance data Celukan Bawang Harbour last 10 years. Then a prediction of traffic flows to goods the next 30 years using multiple linear regression analysis. For the evaluation of the development of the port to analyze the financial feasibility of the port master development plan (RPIP) 10 years from 2014 to 2023 years that compare to the development plan based on a prediction of traffic flows. Based on the evaluation of operating performance, port obtained poor performance. This is evident from the performance indicators in 2013 that the waiting time: 58 hours and BOR value: 88 % above the standard value is specified, while the percentage of effective time / Berthing time: 31.6%, SOR: 6%, Yor: 0% is far below the standard set value. Meanwhile, if the predicted assuming port performance has been improved, the traffic flow of goods grew 10.90% annually. Financial analysis based RPIP port development is not feasible to get the value NPV = -1,521,941,710 BCR value = 0.9828 and a IRR = 11.46%, while the development of port based traffic flow prediction goods with the sensitivity condition cost increase 15% and benefits decrease 15% get decent results with NPV = 12,191,952,255 and BCR value = 1.4546.